Organic syntheses based on name reactions and unnamed reactions - Hassner, Alfred, 1930- (Tetrahedron organic chemistry series, 1994)
Synthetically useful organic reactions or reagents are often referred to by the name of the discoverer(s) or developer(s). Older name reactions are described in text books, but more recently developed synthetically useful reactions that may have been associated occasionally with a name are not always well known. For neither of the above are experimental procedures or references easy to find. In this monograph approximately 500 name reactions are included, of which over 200 represent newer name reactions and modern reagents. Each of these reactions are extremely useful for the contemporary orga.